2020
DOI: 10.1186/s12935-020-01334-4
|View full text |Cite
|
Sign up to set email alerts
|

TMPO-AS1 promotes cell proliferation of thyroid cancer via sponging miR-498 to modulate TMPO

Abstract: Background: Thyroid cancer (TC) is the most frequent endocrine malignancy. Long noncoding RNAs (lncRNAs) have been confirmed to act as significant roles in tumor development. The role of lncRNA TMPO-AS1 in TC is still unclear, so it remains to be explored. The aim of the research is to investigate the role and regulatory mechanism of TMPO-AS1 in TC. Methods: TMPO-AS1 and TMPO expression in TC tumors and cells was detected by TCGA database and QRT-PCR assay respectively. CCK-8, EDU, TUNEL and western blot assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Increasing evidence has confirmed that lncRNA TMPO-AS1 is upregulated in diverse types of cancers, including triple-negative breast cancer, thyroid cancer, and gastric carcinoma. 22–24 Similarly, in the current study, TMPO-AS1 was discovered to be distinctly upregulated in NPC tissue samples. TMPO-AS1 is reported to act as an essential participant in cancer cells’ growth and metastasis.…”
Section: Discussionsupporting
confidence: 74%
“…Increasing evidence has confirmed that lncRNA TMPO-AS1 is upregulated in diverse types of cancers, including triple-negative breast cancer, thyroid cancer, and gastric carcinoma. 22–24 Similarly, in the current study, TMPO-AS1 was discovered to be distinctly upregulated in NPC tissue samples. TMPO-AS1 is reported to act as an essential participant in cancer cells’ growth and metastasis.…”
Section: Discussionsupporting
confidence: 74%
“… 7 TMPO-AS1 can promote cell proliferation of thyroid cancer via sponging miR-498. 19 Consistently, after verifying the direct binding condition between TMPO-AS1 and miR-383-5p, a series of cellular function experiments exhibited that inhibition of miR-383-5p could reverse the low activities of glioma cell proliferation, migration and invasion caused by TMPO-AS1 knockdown, indicating that TMPO-AS1 might sponge miR-383-5p to regulate cellular functions. The functionality of miR-383-5p has been characterized in several types of human cancers.…”
Section: Discussionmentioning
confidence: 71%
“…7 TMPO-AS1 can promote cell proliferation of thyroid cancer via sponging miR-498. 19 Consistently, after verifying the direct binding condition between TMPO-AS1 and miR-383-5p, a series of cellular function experiments exhibited that inhibition of miR-383-5p could reverse the low activities…”
Section: Discussionmentioning
confidence: 76%
“…Numerous studies have revealed that TMPO-AS1 contributes to tumorigenesis. However, most of them suggest that this is mediated via a TMPO-AS1-miRNA-mRNA axis [17,18,51,52], while others propose that TMPO-AS1 forms RNA-RNA complexes to regulate gene expression [19,55]. Very recently, a study has shown that TMPO-AS1 promotes BC cell growth via a TMPO-AS1/miR-98-5p/EBF1 positive feedback loop [51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have demonstrated that upregulated TMPO antisense RNA 1 (TMPO-AS1) serves as competing endogenous RNA to sponge microRNAs (miRNAs) in multiple carcinomas including hepatocellular carcinoma, thyroid cancer, lung adenocarcinoma, and breast cancer [17,18,19,20]. However, whether TMPO-AS1 plays a role by interacting with other molecules in BC is an interesting question requiring further investigation.…”
Section: Introductionmentioning
confidence: 99%